Theorizing the Emergence of Change in Daily Living: Developing a Contextual Framework for Social Work Practice. - Keenan, Elizabeth King (2008)
Keywords: dept.swk; faculty_collection; sabbatical_report

Early Detection of Schizophrenia: Phenomenological Markers. - Rakfeldt, Jaak (2000)
Keywords: dept.swk; faculty_collection; sabbatical_report

Diversity, Oppression, and Social Functioning: Person-in-Environment Assessment and Intervention - Appleby, George A. (Pearson/Allyn and Bacon, 2007)
Keywords: Social work with minorities; Person-in-environment system; dept.swk; faculty_collection

A Dream and a Plan: A Woman's Path to Leadership in Human Services - Gardella, Lorrie Greenhouse; Haynes, Karen S.; National Association of Social Workers (NASW Press, 2004)
Keywords: Administration; Leadership; Promotions; United States; United States; Career development; United States; Human services; United States; Women executives; United States; Women social workers; Women social workers; dept.swk; faculty_collection

Working-Class Gay and Bisexual Men - Appleby, George A. (Harrington Park Press, 2001)
Keywords: Services for; Services for; Bisexual men; Social work with gays; Gays; dept.swk; faculty_collection

Diversity, Oppression, and Social Functioning: Person-in-Environment Assessment and Intervention - Appleby, George A.; Colon, Edgar; Hamilton, Julia (Allyn and Bacon, 2001)
Keywords: Social work with minorities; Person-in-environment system; dept.swk; faculty_collection

Introduction - Flynn, D.S.; Siegel, E. (Gerontology and Geriatrics Education, 2001)
0 citations (Crossref) [2023-10-31]
Keywords: dept.swk

The supervisor in aging services - Corley, C.S.; Takamura, J.; Siegel, E. (Supervision as Collaboration in the Human Services: Building a Learning Culture, 2004)
Journal Abbreviation: Superv. as Collaboration in the Hum. Services: Building a Learning Culture
Keywords: dept.swk

The impact of terrorism, terror and trauma on children: Implications for treatment - Marvasti, J.A.; Dripchak, V.L. (American Journal of Forensic Psychiatry, 2004)
Keywords: alcohol; antidepressant agent; article; battle injury; behavior therapy; beta adrenergic receptor blocking agent; case report; child; child behavior; cognitive therapy; cultural factor; cyproheptadine; dept.swk; family violence; fear; female; fluoxetine; human; imipramine; immune system; male; nightmare; paroxetine; play therapy; posttraumatic stress disorder; propranolol; psychotrauma; self medication; serotonin uptake inhibitor; sertraline; sexual abuse; street drug; terrorism; tricyclic antidepressant agent; ⛔ No DOI found

Managing school discipline and implications for school social workers: A review of the literature - Cameron, M. (Children and Schools, 2006)
School disciplinary policies and practices are essential features of life in U.S. schools. Conventional approaches to school discipline - including conduct codes and security methods, suspension, corporal punishment, and teachers' methods of managing student behaviors - rely primarily on deterrence, control, and punishment to maintain order. However, approximately 40 years of research, chiefly in education and psychology, has demonstrated that these policies and practices are often associated with and can contribute to increased disorder in schools and behavioral and academic problems among students. Furthermore, school discipline is sometimes administered prejudicially to those students who may be the most vulnerable. School social workers and all social workers working with children and youths can help schools adopt effective and nonpunitive disciplinary approaches. Key professional actions include advocacy for schoolchildren subject to unfair and overly punitive discipline; educating teachers and administrators about the potential harm associated with conventional disciplinary practices; educating school personnel about effective, nonpunitive approaches; and creating a public campaign to generate popular support for the reform of iatrogenic school disciplinary practices. © 2006 National Association of Social Workers.
48 citations (Crossref) [2023-10-31]
Keywords: Children; Discipline; Punishment; School social work; Schools; dept.swk

School discipline and social work practice: Application of research and theory to intervention - Cameron, M.; Sheppard, S.M. (Children and Schools, 2006)
Research has identified a relationship between school disciplinary actions and poor academic and psychosocial functioning of students subjected to them. The ways in which school discipline is a direct contributor to students' academic and psychosocial difficulty needs to be further established empirically. Several theories, based in existing research and theory in sociology of education and educational psychology, have been proposed to explain the school discipline - student dysfunction relationship. They generally suggest three pathways: disciplinary actions may contribute to students' psychological problems; student misbehavior may be encouraged through ineffective and unintentionally paradoxical learning experiences; and disciplinary practices may damage students' relationship with school. School social workers and others working with children who have been disciplined at school can use these research findings and theories as an assessment framework to guide their interventions.The awareness of the iatrogenic potential of school discipline and informed assessment can support a range of evidence-based alternatives to school discipline. © 2006 National Association of Social Workers.
27 citations (Crossref) [2023-10-31]
Keywords: Assessment; Children; Discipline; School social work; Schools; dept.swk

Social work practice with LGBT people within organizations - Appleby, G.A.; Colon, E. (Soc. Work Pract. with Lesbian Gay Bisexual and Transgender People: Second Ed., 2008)
Journal Abbreviation: Soc. Work Pract. with Lesbian Gay Bisexual and Transgender People: Second Ed.
Keywords: dept.swk

A case for developing the emotional capacities of social workers: A commentary on “Promoting self-awareness: Infant observation training as a model” - Bliss, S (Smith College Studies in Social Work, 2005)
tex.unique-id: ISI:000232698200005
Keywords: dept.swk; ⚠️ Invalid DOI

Micro ruptures and repairs in the beginning phase of cross-cultural psychotherapy - Keenan, Elizabeth; Tsang, A.; Bogo, Marion; George, Usha (Clinical Social Work Journal, 2005)
The article discusses misunderstandings and misattunements that occur in the beginning phase of cross-cultural psychotherapy. Sources of micro ruptures are outlined, including client maladaptive patterns, therapist misunderstandings, cross-cultural misunderstandings due to cultural variations, and asymmetrical power relations involving the impact of prior experiences or current therapy practices. Multiple clinical vignettes illustrate the rupture/repair process, drawing on Safran and Muran's (2000) list of direct and indirect techniques., (C)2005 Kluwer Academic Publishers
12 citations (Crossref) [2023-10-31] Place: (C)2005 Kluwer Academic Publishers
Keywords: Beginning phase of psychotherapy; Cross-cultural psychotherapy; Rupture and repair; Therapeutic relationship; beginning phase of psychotherapy; cross-cultural psychotherapy; dept.swk; rupture and repair; therapeutic relationship

From sociocultural categories to socially located relations: Using critical theory in social work practice - Keenan, EK (Families in Society-the Journal of Contemporary Human Services, 2004)
This article applies concepts from critical social theories to shift the profession's discourse from the center-margin relations of generalist-multicultural practice to a model of socially located cross-cultural client-worker relationships. Critical theories examine patterns and meanings enacted within and between people in specific social locations at specific points in history that express particular relations of culture, power, and identity. This framework can help social workers listen, explore, conceptualize, and intervene in a more complex and effective manner. The article summarizes key themes in critical theories, redefines how social workers can use knowledge for practice, and concludes with discussion of a case illustration.
12 citations (Crossref) [2023-10-31] tex.unique-id: ISI:000226071200011
Keywords: dept.swk

Cacophony, polyphony or fugue: Exploring sociocultural concepts with social work students - Keenan, Elizabeth King; Miehls, Dennis; Moffatt, Kenneth; Orwat, John; White, Joyce (Smith College Studies in Social Work, 2004)
This paper documents some dialogue among the authors that emerged as each taught Master of Social Work students a course in sociocultural concepts. The instructors taught this required course from a common syllabus and the discussion reflects the authors' experiences in the delivery of the course material. At the time these dialogues took place, the instructors had recently changed the course format. Rather than teaching sociocultural concepts in isolation (eg. a class on sexism, a class on ageism, etc.), the instructors crafted the course content around central themes. Postmodern theories underscore much of the course content, and are synthesized both in this course and across the curriculum with feminist, psychodynamic, and cross-cultural practice theories. The paper begins by summarizing key post-modern theories that frame the course. Then, the authors respond to formulated questions that address multiple forms of identity development, ambiguity, and competing student ideologies that are manifest in classroom dynamics. Finally, the authors discuss their respective pedagogical and theoretical views and discuss their classroom experiences.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/049-164-803-188-190 tex.type: [object Object]
Keywords: dept.swk

Working models: A tool for synthesizing psychology, culture, and power in everyday experiences and internal representations - Keenan, Elizabeth King (Smith College Studies in Social Work, 2003)
As social beings, we experience ourselves through interactions with others in daily routines that participate in the cultural practices and power relations of broader social structures. Social workers, and social scientists in general, however, have had difficulty conceptualizing and synthesizing this way of being in the world. This paper attempts to respond to that gap by discussing how clinical social workers can use the concept of working models as a tool for listening and understanding in psychotherapy. Utilizing a case example, the paper will discuss three working models, the enactment of power relations, cultural practices, and psychological processes, which provide an integrative framework to inform clinical work.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/018-182-490-831-257 tex.type: [object Object]
Keywords: dept.swk

Distance learning in gerontological education: results and implications of a national survey - Tompkins, Catherine J.; Siegel, Elbert (Gerontology & Geriatrics Education, 2001)
This article reports data collected from a national survey of the Association for Gerontology in Higher Education’s (AGHE) member institutions conducted in 1998. The purpose was to explore current usage of distance learning in gerontological education. The findings suggest that distance learning is being implemented within various programs throughout the country with many others showing an interest. The strengths and limitations of using distance learning in gerontological education are discussed. [Article copies available for a fee from The Haworth Document Delivery Service: 1-800-342-9678. E-mail address: <getinfo@haworthpressinc.com> Website: <http://www.HaworthPress.com>]. © 2001 by The Haworth Press, Inc. All rights reserved.
6 citations (Crossref) [2023-10-31] Citation Key Alias: pop00279 tex.type: [object Object]
Keywords: dept.swk

Practice and theoretical knowledge-based theory for clinical and policy practice - Appleby, George Alan (Journal of Gay and Lesbian Social Services, 2001)
SUMMARY: Practice with working-class gay and bisexual men draws upon an ecological framework with a strengths perspective, which emphasizes the roles of culture, values, social class, social identity development, social categorization, social comparison, oppression and power, diversity, and stigma. This practice is based upon a process of developing an assessment and selecting a range of human service interventions. Ethnographic studies were conducted throughout the United States and Canada using a broad-based sample of working-class men to enhance our understanding of their needs and effective ways of helping. © 2001, Taylor & Francis Group, LLC.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/170-732-264-616-422 tex.type: [object Object]
Keywords: And intervention; Assessment; Culture; Diversity; Ecology; Individual and group identity; Oppression and power; Social class; Stigma; Strengths; Values; dept.swk

"It was just realizing... that life isn't one big horror": A qualitative study of supported socialization - Davidson, L.; Haglund, K.E.; Stayner, D.A.; Rakfeldt, J.; Chinman, M.J.; Tebes, J.K. (Psychiatric Rehabilitation Journal, 2001)
This report describes the qualitative component of a large-scale study of supported socialization. Paralleling the recent advances made through supported housing, supported employment, and supported education, this approach seeks to increase the involvement of individuals with psychiatric disabilities in naturally occurring social and recreational activities in community settings of their choice. After a review of social relationships and psychiatric disability, we describe the Partnership Project and present findings from a series of qualitative interviews conducted with a subsample of participants. We then discuss the implications of these findings for the community integration of individuals with psychiatric disabilities.
90 citations (Crossref) [2023-10-31]
Keywords: adult; article; clinical article; dept.swk; education; employment; female; health program; housing; human; human relation; integration; life; male; mental disease; questionnaire; recreation; socialization; support group; therapeutic community

A new perspective: the common factors model as a foundation for social work practice education - Cameron, Mark; Keenan, Elizabeth King (Journal of Teaching in Social Work, 2009)
Foundation social work practice education is critical to the preparation of BSW practitioners for professional practice and the establishment of a theoretical and skill base upon which graduate students may build competencies in the advanced curriculum. Issues in the foundation practice curriculum may hinder this development. The common factors model holds promise as an organizing framework for foundation social work practice education. This model may help to resolve some key issues in social work and social work education, and may provide a useful, coherent, and empirical base for the foundation practice curriculum. © Taylor & Francis Group, LLC.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/061-482-221-756-184 tex.type: [object Object]
Keywords: Common factors; Direct practice; Foundation curriculum; Practice education; dept.swk; peer-reviewed

Teaching organization theory and practice: an experiential and reflective approach - Cameron, Mark; Turkiewicz, Rita M; Holdaway, Britt A; Bill, Jacqueline S; Goodman, Jessica; Bonner, Aisha; Daly, Stacey; Cohen, Michael D; Lorenz, Cassandra; Wilson, Paul R; Rusk, James (Journal of Teaching in Social Work, 2009)
The organization is often the overlooked level in social work's ecological perspective. However, organizational realities exert a profound influence on human development and well-being as well as the nature and quality of social work practice. This article describes a model of teaching organization theory and practice which requires master's social work students to assess their school of social work as well as their field placement agencies. Teaching organization theory and practice experientially may help students understand how organizations influence practice and empower them to see organization practice as a legitimate and important aspect of their work.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/022-043-403-165-052 tex.type: [object Object]
Keywords: Field education; Macro; Organization; Practice; Teaching; dept.swk; peer-reviewed

Third Space Activities and Change Processes: An Exploration of Ideas from Social and Psychodynamic Theories. - Keenan, Elizabeth; Miehls, Dennis (Clinical Social Work Journal, 2008)
Discussions pertaining to culture, power and/or identity frequently create tensions that are enacted by dyads and groups within schools, workplaces and communities. Although tensions can easily escalate into conflict or violence, we have observed that these tensions can serve as prompts that promote a change process. When individual perspectives are challenged, some participants are able to dissemble their views and consider other perspectives from which new understandings and views emerge. At times, when groups seem to be on the threshold of overt conflict, some participants engage in processes that examine the tension, explore new possibilities, and alter the view of one's subjectivity. We suggest that these activities occur as momentary states in psychological spaces conceptualized as third spaces (Bhabha, The location of culture. London: Routledge, 1994). In this paper, we use concepts from psychodynamic and social theories to describe the conditions that coalesce to form states of mind (nepantla) (Anzaldua, Borderlands/La Frontera: The new mestiza. San Francisco: Aunt Lute Books, 1999; Interviews Entrevistas. New York: Routledge, 2000) and the ability to engage in new relational possibilities (third space activities) with dyads and groups, outside of psychotherapy. The conditions include: critical consciousness, regulation, recognition, and responsibility. We then describe how such momentary experiences can subsequently result in an examination of one's subjectivity, particularly as it pertains to issues regarding culture, power, and identity. Throughout the paper we provide four examples from various settings to illustrate these concepts and processes. Given the increasing racial/ethnic diversity of clients and clinical social workers in North America, this concept of third spaces holds particular relevance for contemporary clinical social work practice., (C)2008 Kluwer Academic Publishers
10 citations (Crossref) [2023-10-31] Place: (C)2008 Kluwer Academic Publishers
Keywords: Change processes; Psychodynamic theory; Social theory; Third space activities; dept.swk

Posttraumatic play: Towards acceptance and resolution - Dripchak, Valerie L. (Clinical Social Work Journal, 2007)
Many children who experience trauma demonstrate it through posttraumatic play (PTP). This type of play is seen by professionals as a repetitive reenactment of the traumatic event within the child's play. Reliving the event in this way may serve to retraumatize the child and lead to other psychiatric or behavioral problems. This article examines the issues surrounding childhood trauma and PTP. It uses a case study to illustrate the phases of a play therapy approach that incorporates Ericksonian principles, in order for the child to achieve resolution and acceptance. The countertransference issues that a clinician may encounter also are discussed.
14 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/049-629-250-370-634 tex.unique-id: [object Object]
Keywords: Play therapy; Posttraumatic play; Retraumatize; Trauma in children; dept.swk

Lesbian mothers with planned families: A comparative study of internalized homophobia and social support - DeMino, Kathleen A.; Appleby, George; Fisk, Deborah (American Journal of Orthopsychiatry, 2007)
This study compared the perception of social support and the degree of internalized homophobia for two demographically similar groups: lesbians with planned families and lesbians who did not have children. Results found that lesbians with planned families perceived significantly less social support from friends overall, from gay men and lesbian friends specifically, and more support from their families-of-origin than lesbians who did not have children. Lesbians with planned families also reported significantly higher internalized homophobia specific to disclosure of sexual identification. The authors suggest that selective disclosure may be an adaptive response rather than a true measure of internalized homophobia.
22 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/091-948-881-682-440 tex.unique-id: [object Object]
Keywords: Adult; Attitude; Child; Family Planning Services; Female; Homosexuality; Female; Humans; Internalized homophobia; Lesbian mothers; Maternal Behavior; Mothers; Percerption of social support; Planned families; Questionnaires; Self Concept; Social Support; adult; article; controlled study; demography; dept.swk; family; female; gender identity; homophobia; human; lesbian; male homosexual; social support

Diagnosing conduct problems of children and adolescents in residential treatment - Cameron, Mark; Guterman, Neil B (Child Care Quarterly, 2007)
This naturalistic study of diagnostic practice in residential treatment agencies for children investigated the use of the DSM-IVconduct disorder diagnosis and its association with residents' externalizing behaviors. The conduct disorder (CD) diagnosis was a poor predictor of participants' externalizing behaviors during their first few months in residence. Additionally, the assignment of the diagnosis was associated with the gender and race of study participants. Decisions of admissions personnel and practitioners in residential treatment facilities regarding their externalizing clients may not be well-served by use of DSM diagnoses. Assessments of caregivers may prove a useful adjunct to DSM diagnoses. © 2007 Springer Science+Business Media, LLC.
22 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/001-610-397-897-543 tex.type: [object Object]
Keywords: Adolescents; Children; Conduct disorder; DSM-IV validity; Diagnosis; Residential treatment; dept.swk

Assertive outreach: An effective strategy for engaging homeless persons with substance use disorders into treatment - Fisk, Deborah; Rakfeldt, Jaak; McCormack, Erin (American Journal of Drug and Alcohol Abuse, 2006)
The purpose of this study was to examine substance abuse treatment referrals that were made by outreach workers in a homeless outreach project. Ten outreach workers completed questionnaires on each of their clients who they had referred to a substance abuse treatment program over the previous year. Additional data was collected on the client's motivation level at the point the referral was made, which agencies the client was referred to, and if the client was rejected from any of the treatment programs. Bivariate correlation analyses were used to examine relationships between the variables. Of 73 project clients who were referred to substance abuse treatment in a one-year period of time, 41% successfully entered treatment. As might be expected, there was a statistically significant relationship between clients' motivation level and completed referral, and between referrals made and program acceptance. This study provides evidence that assertive outreach is effective in engaging and linking homeless persons with substance use disorders to substance abuse treatment services.
26 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/063-067-831-831-545 tex.unique-id: [object Object]
Keywords: Adolescent; Adult; Assertive outreach; Community-Institutional Relations; Female; Homeless Persons; Homeless populations; Humans; Male; Middle Aged; Substance abuse; Substance-Related Disorders; Treatment Outcome; adult; article; assertiveness; correlation analysis; dept.swk; drug dependence treatment; female; homelessness; human; major clinical study; male; mental health service; motivation; patient referral; social work; social worker; statistical significance; substance abuse